Analyses et réflexions à partir du symposium « Éduquer au vivre ensemble ou éduquer à la citoyenneté » - Hélène Marquié-Dubié (Éducation et Socialisation)
This article tries to synthetize the interventions developed by the professionals and researchers who participated in the symposium ‘Educate to live together or educate to citizenship’ offered by Yveline Fumat as part of the symposium ‘The education of very young children: social and instructive stakes of reception in different institutional forms’. From different experiments (E.A.J.E., Nursery schools, Green Houses, etc), were discussed the first needs of the very young child(emotional and cognitive needs) and the specific answers which are brought by each of structure together with their missions. In the same way the question of learning as vectors of development as much as material of it. The question of how to train the professionals who accompany the children in the different places appears as essential: knowing how to support the development of self-government and thought requires specific knowledge about the process.